The Influence of Leverage, Liquidity and Profitability toward Tax Avoidance in Property and Real Estate Companies Listed on Indonesia Stock Exchange - Ciptawan; Wenny (Future Science, 2024)
Tax avoidance is an effort to avoid tax which have an impact on tax liabilities that are carried out by still complying in the tax provisions and do not violate the tax provisions predetermined. The objective of this research is to analyze whether Leverage, Liquidity and Profitability have a significant influence toward Tax Avoidance in Property and Real Estate Companies Listed on the Indonesia Stock Exchange from the year 2020-2022. This research method is using quantitative approach and collection of secondary data through Financial Report listed on the Indonesia Stock Exchange. All of the Property and Real Estate Companies listed on the Indonesia Stock Exchange are the population in this research. 15 companies are taken as the number of samples through purposive sampling method and result in 45 companies in total with three year observations. The data analysis method in this research includes: descriptive statistics, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, t-test, f-test, and coefficient of determination. Based on the data analysis, the findings of this research shows that Leverage partially does not have a significant influence toward tax avoidance. Liquidity partially does not have a significant influence toward tax avoidance. Profitability partially has a significant influence toward tax avoidance. Leverage, Liquidity and Profitability simultaneously have a significant influence toward tax avoidance.